Lead and other Metals in Riyadh Atmosphere and Its Relationship to Traffic Volume and Industrial Activities - Al-Shayeb, S.M. (Asian Journal of Chemistry, 2010)
The concentrations of Pb, Zn, Cu, Cd, Cr and Ni in atmospheric particulates have been determined at nine main roads and the three industrial locations (first industrial city, second industrial city and the industrial workshops area) in Riyadh city. The experimental results obtained, show that the automobile emission is the predominant source for Pb, Zn, Cu and Cd pollution was observed. The highest lead concentration was observed at King Fahad road and the industrial workshops area (3.60 and 3.30 μg m–3 respectively), which is higher than the European community (EC) limit (2 μg m–3). The highest concentrations of Zn, Cu, Cd, Cr and Ni were recorded at the industrial workshops area, which shows to be one of the main sources of these metal pollutants in Riyadh city.